An unusual case of an ectopic bronchogenic cyst at the terminal ileum - Alyssa Greenwood Francis; Natalie Merchant; Jonthan Lavezo; Alonso Andrade (Elsevier, 2022)
Bronchogenic cysts are rare congenital malformations, with a suspected prevalence between 1 per 42,000 to 68,000 hospital admissions. Since these lesions are often asymptomatic, they are undetected until later decades of life. Most ectopic bronchogenic cysts are located intrapulmonary (20-30%), but they have been found in the pericardia, diaphragm, and retroperitoneum. We present an unusual case of a 20-year-old female with an ileal ectopic bronchogenic cyst who presented with right lower quadrant abdominal pain, and imaging which revealed a cystic lesion at the terminal ileum. Due to the severity of her symptoms, the patient underwent a diagnostic laparoscopy with conversion to laparoscopic-assisted open ileocecectomy with ileocolonic anastomosis. Pathology identified the lesion as an ectopic bronchogenic cyst. This case demonstrates the difficulty in identifying ectopic bronchogenic cysts on radiographic imaging and the importance of maintaining a broad differential for right lower quadrant abdominal pain in the pediatric population, considering the infectious and malignant potential of these cysts.